Activation of HIF1α ubiquitination by a reconstituted von Hippel-Lindau (VHL) tumor suppressor complex - Kamura, Takumi (The National Academy of Sciences, 2000)
Mutations in the VHL tumor suppressor gene result in constitutive expression of many hypoxia-inducible genes, at least in part because of increases in the cellular level of hypoxia-inducible transcription factor HIF1α, which in normal cells is rapidly ubiquitinated and degraded by the proteasome under normoxic conditions. The recent observation that the VHL protein is a subunit of an Skp1-Cul1/Cdc53-F-box (SCF)-like E3 ubiquitin ligase raised the possibility that VHL may be directly responsible for regulating cellular levels of HIF1α by targeting it for ubiquitination and proteolysis. In this report, we test this hypothesis directly. We report development of methods for production of the purified recombinant VHL complex and present direct biochemical evidence that it can function with an E1 ubiquitin-activating enzyme and E2 ubiquitin-conjugating enzyme to activate HIF1α ubiquitination in vitro. Our findings provide new insight into the function of the VHL tumor suppressor protein, and they provide a foundation for future investigations of the mechanisms underlying VHL regulation of oxygen-dependent gene expression.